Bacterial contamination of protective lead garments in an operating room setting. Issue 6 (November 2020) - Gilat, Ron; Mitchnik, Ilan; Beit Ner, Eran; Shohat, Noam; Tamir, Eran; Weil, Yoram A; Lazarovitch, Tsilia; Agar, Gabriel
Background: Protective lead garments (PLG) worn in the operating room are a potential source for bacterial colonisation and thus may increase the risk of intraoperative infection. The clinical significance of such bacterial contamination has yet been established. Although disinfection protocols have been employed, their effectiveness is also unknown. Objective: We sought to describe and compare the bacterial profile of PLGs with a focus on common pathogens involved in surgical site infections (SSI) and prosthetic joint infections (PJI). Methods: We studied body aprons and neck-thyroid protective shields. We sampled 20 body aprons and 21 neck PLGs, swabbing the inside and outside of the PLGs. Swabs were cultured on different media and the results were assessed and compared. Results: Of PLGs, 87.8% were contaminated. The neck-thyroid shield PLGs was generally more contaminated than body apron PLGs and exhibited significantly higher loads of Staphylococcus epidermidis ( P = 0.048). Other pathogen cultured were Micrococcus spp., Acinetobacter lwoffii ( A. lwoffii ), Bacillus species ( Bacillus spp.), Moraxella osloensis ( M. osloensis ) and Pseudomonas stutzeri ( P. stutzeri ). No other common pathogens associated with SSI or PJI were detected. Conclusions: PLGs are heavily contaminated despite regular cleaning protocols. Neck PLGs are highly contaminated with potentially infectious agents. As neck PLGs are often directly exposed above the surgical sterile gown and the surgical field, measures should be undertaken to reduce their exposure and bacterial load, perhaps by suggesting users consider avoiding the use of intraoperative fluoroscopy when possible or alternatively supporting the use of body exhaust suits when PLGs are needed.